1986
DOI: 10.1159/000183690
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Ionized Calcium with Normal PTH and Total Calcium Levels in Normal-Function Kidney Transplant Recipients

Abstract: Hypercalcemia is a postrenal transplant complication. We found a high frequency of elevated plasma ionized calcium values (65.8%) in 41 normal-function renal graft recipients. In 8 patients increased free calcium was associated with high PTH levels, whereas in 19 PTH was not increased but free calcium was high. In the other 14 patients both free calcium and PTH were in the normal range. The mean transplant duration was different in the three groups: shorter in high PTH patients, longer in normal free calcium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Comparable studies are scarce in literature. Vezzoli et al (20) reported iCa levels exceeding 1.29 mmol/L in 27 of 41 renal transplant recipients, which represent a prevalence rate that is close to ours. Most studies assessing post-transplant calcium metabolism thus far analyzed uncorrected or albumin-corrected tCa levels and reported substantially lower prevalences of hypercalcemia (7)(8)(9)(10)(11)21,22).…”
Section: Discussionsupporting
confidence: 89%
“…Comparable studies are scarce in literature. Vezzoli et al (20) reported iCa levels exceeding 1.29 mmol/L in 27 of 41 renal transplant recipients, which represent a prevalence rate that is close to ours. Most studies assessing post-transplant calcium metabolism thus far analyzed uncorrected or albumin-corrected tCa levels and reported substantially lower prevalences of hypercalcemia (7)(8)(9)(10)(11)21,22).…”
Section: Discussionsupporting
confidence: 89%
“…In adult renal transplant recipients, persistent high serum PTH levels are thought to result in hypercalcemia [9,17] and hypophosphatemia [10]. In our study, hypercalcemia after transplantation was seen in 28% and 23% at 6 months and 12 months, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…57], hypercalciuria [13], hypophosphataemia with hyperphosphaturia [52], and subnormal in testinal calcium absorption [13] have been reported. Persistent secondary hyperpara thyroidism may be normo-or hypercalcaemic [47,[51][52][53]. Reduced phosphate reabsorption in renal tubules seems not to be related or predominantly related to PTH af ter renal transplantation [52], Unexpectedly, in some KTP normal plasma PTH and total calcium levels in the presence of highly ion ized calcium have been reported [51].…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…Persistent secondary hyperpara thyroidism may be normo-or hypercalcaemic [47,[51][52][53]. Reduced phosphate reabsorption in renal tubules seems not to be related or predominantly related to PTH af ter renal transplantation [52], Unexpectedly, in some KTP normal plasma PTH and total calcium levels in the presence of highly ion ized calcium have been reported [51]. Thus, it seems that hyperparathyroidism may per sist during the first post-transplant period and that this complication evolves towards normalization of the blood chemistry values passing through a period of inappropriate PTH secretion with elevated ionized calcium [51], The incidence of bone abnormalities during the post-transplant period does not only depend upon the functional quality of the graft, but also upon the degree of phos phate depletion, the amount of total gluco corticoids administered, and the nutritional and vitamin D status before and after trans plantation.…”
Section: Parathyroid Hormonementioning
confidence: 99%
See 1 more Smart Citation